Reduced Order Methods for Imaging and Time Series Analysis - Ozsar, Ege (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Electrical Engineering.; Advisor: Eric Miller.; Committee: Misha Kilmer, Eric de Sturler, Shuchin Aeron, and Eric Miller.; Keywords: Engineering, Electrical engineering, and Artificial intelligence.